Motivasi Kerja, Manajemen Kinerja Petugas Surveilans Epidemiologi Puskesmas dan Angka Notifikasi Kasus Tuberkulosis di Kabupaten Jepara - Maharani Latifah; Suharyo Suharyo (Dian Nuswantoro Semarang, 2017)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Beginning in 2015, the main indicators of TB control programs nationally are TB Case Notification Rate (CNR) and Success Rate of Treatment of Succes Rate (TSR). In 2014 the CNR showed 42.1% and in 2015 49.4% or the case finding in Jepara increase 7.3%. It indicated that the program have not reached the target that should decrease 3-4% per year. This was quantitative research, with cross sectional approach. The subjects were twenty one TB surveillance officers at the pubic health centers in Jepara Regency.The questionnaire condatasisted of motivation and performance of management was used for collecting data. The Chi Square test was used for analyzing data with p-value 0,05 and confidence interval 95%. Based on the research, there was relationship between motivation and CNR (p-value 0,035) but performance management was not related to CNR (p-value 0,131) The TB surveillance officers have to record and report properly, correctly and on time. The head of puskesmas continue to motivate the officers and TB officer in Jepara Health Office should monitor the activities that carried out by each puskesmas.Keywords: work motivation, performance management, CNR, TB